2019
DOI: 10.1016/j.renene.2018.08.090
|View full text |Cite
|
Sign up to set email alerts
|

Non-isothermal thermogravimetric kinetic analysis of the thermochemical conversion of human faeces

Abstract: The “Reinvent the Toilet Challenge” set by the Bill & Melinda Gates Foundation aims to bring access to adequate sanitary systems to billions of people. In response to this challenge, on-site sanitation systems are proposed and being developed globally. These systems require in-situ thermal treatment, processes that are not well understood for human faeces (HF). Thermogravimetric analysis has been used to investigate the pyrolysis, gasification and combustion of HF. The results are compared to the thermal behav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…The frequency factor and reaction order values are a guide for estimating the reaction rate [ 50 ]. In addition, a non-integer order of reaction was found at every investigated zone, which demonstrated that the thermochemical conversion process of the samples took place in a complex reaction mechanism [ 68 ].…”
Section: Resultsmentioning
confidence: 99%
“…The frequency factor and reaction order values are a guide for estimating the reaction rate [ 50 ]. In addition, a non-integer order of reaction was found at every investigated zone, which demonstrated that the thermochemical conversion process of the samples took place in a complex reaction mechanism [ 68 ].…”
Section: Resultsmentioning
confidence: 99%
“…This mechanical flush -a rotating bowl and rubber swipe activated by moving the toilet lid -separates the user from a tank underneath the toilet pan (Tierney, 2014;Tierney, 2017). Solids are separated through settling and displacement, transported by an screw conveyor (Mercer et al, 2016) and subsequently dried and combusted (Fidalgo et al, 2019;Onabanjo et al, 2016), while the liquid fraction is extracted through a weir and purified through membrane processes (Kamranvand et al, 2018;Wang et al, 2017), driven by the heat of the combustion, which is transferred via a heat exchanger (Hanak et al, 2016). The toilet pedestal, including the mechanical flush, the screw conveyor, and the liquid weir are considered the NMT's front end.…”
Section: Methodsmentioning
confidence: 99%
“…Thermogravimetric analysis (TGA) enables material characterisation because it measures the change in mass of a material with respect to time or temperature, as the material is subjected to controlled temperature and heating changes 11 , 12 . Based on TGA techniques, drying rates are shown to vary from one sludge to another, depending on sample composition, origin, treatment method and retention time 13 , 14 .…”
Section: Introductionmentioning
confidence: 99%